DEVELOPMENT OF THE METHOD OF DESIGNING THE MICRO SCREW EXTRUDER OF A 3D PRINTER - POLISHCHUK, ANDRII; POLISHCHUK, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article deals with the development of a design method for a 3D printer extruder screw. The key aspects that must be applied during design are described. The main mechanical properties that should be taken into account when designing the screw element of the extruder are given. Various designs of screws, their advantages and disadvantages are considered. A single-screw extruder was selected for a 3D printer, which uses granules, crushed waste polymer materials as raw materials. It is proposed to use a three-zone cylindrical one-way screw with a constant pitch and without a degassing zone of the screw for processing granules or crushed polymer particles. Recommended for screw extruders that do not require high dosing pressure of molten polymer material and that process non-porous homogeneous polymer materials, single-zone screws with a constant pitch and depth of screw cutting. Their use in the processing of cut strips from plastic waste is proposed. The main geometric parameters of the screw with a constant pitch and a variable depth of the screw channel were determined for designing. The diameter for the 3D printer extruder has been selected. Dependencies are given for determining the length of the screw, the pitch of the screw thread, the width of the crest of the turn, the angle of elevation of the screw line of the screw thread, and the depth of the screw channel of the screw. Dependencies are given for determining the boundaries of feeding, plasticizing, and dosing zones. The degree of screw compression was determined for the main polymer materials used in 3D printing. The geometry of screws depending on the degree of compression for different materials is given. A formula is presented for determining the volume performance of a 3D printer extruder depending on the design of the dosing zone and nozzle resistance. The formulas for determining the forward flow constant, the reverse flow constant and the flow constant of the flowing material and the dependence of the coefficients characterizing the design of the auger with a variable cutting depth are presented. The geometric parameters of screws with a constant pitch and depth of screw cutting and expressions for their determination are described.
Keywords: polymer material; 3D printing; 3D printer; extruder; screw; screw diameter; screw length; degree of compression